Citizens at the crossroad: Intimate citizenship and intersectionality in the case of women with disabilities - Pérez de la Merced, Elena (Investigaciones Feministas (Feminist Research), 2017)
This paper undertakes a review from an intersectional point of view of the concept of intimated citizenship coined by Plummer. Specifically, it represents an approach to the disabled women intimate citizenship focused on Law 39/2006 of Promotion of the Autonomous Life and Care of People in situation of dependence. We analyse this Law 39/2006 from an intersectional point of view in order to address its scope and limitations regarding the deepening of democratic process, in particular, reproductive rights of women with disabilities.
Keywords: Intersectionality; intimate citizenship; gender; disability; sexual and reproductive rights